Pemberdayaan kepada Pelaku Pariwisata dalam Memberikan Pertolongan Pertama Korban Tenggelam di Wilayah Pantai Mertasari Sanur - AA. Istri Dalem, Hana Yundari; Puspawati, Ni Luh Putu Dewi; Asdiwinata, I Nyoman; Dilisca, Ni Luh Putu Nova; Prasetya, Didik (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2025)
Background: Bali Province is a tourist destination which makes Bali have the potential for drowning cases. It is very important to initiate first aid immediately so that the victim can avoid death or more severe disability. Therefore, knowledge regarding techniques for providing basic life support and handling drowning victims. Tourism actors in coastal areas have the first opportunity to help drowning victims. Objective: To determine the knowledge and skills of the community in providing first aid to drowning victims. Method: Lectures and discussions to explain knowledge and techniques in handling or providing first aid to drowning patients. The media used are leaflets and flipcharts. The targets for this community service are tourism actors, namely travel agent employees in the Mertasari Sanur beach area, totaling 50 employees. Results: Before being given education about handling drowning victims, 66.7% of participants had poor knowledge and only 33.3% of participants had good knowledge and 76.7% of participants had very good knowledge and 23.3% had good knowledge after learning about handling drowning victims. Conclusion: There was an increase in participants' knowledge and skills in providing first aid to drowning victims.